2018
DOI: 10.28991/cej-0309186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Near Fault and Far Fault Ground Motions on Nonlinear Dynamic Response and Seismic Improvement of Bridges

Abstract: In this study, the dynamic response of bridges to earthquakes near and far from the fault has been investigated. With respect to available data and showing the effects of key factors and variables, we have examined the bridge's performance. Modeling a two-span concrete bridge in CSI Bridge software and ability of this bridge under strong ground motion to near and far from fault has been investigated. Nonlinear dynamic analysis of time history includes seven records of past earthquakes on models and it was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The response of the Sutong Cable stayed bridge with the forward directivity with fling step ground motions and the artificial pulses near-fault pulse-type ground motions were studied by the researchers and the results shows that the fling step ground motions which have low PGV/PGA, enforce larger deformation and internal forces over the structure than the forward directivity motions (fig. 5) (Li et al, 2017;Hajali et al, 2018).…”
Section: Effect Of Near-fault Earthquake On Bridge Structuresmentioning
confidence: 99%
“…The response of the Sutong Cable stayed bridge with the forward directivity with fling step ground motions and the artificial pulses near-fault pulse-type ground motions were studied by the researchers and the results shows that the fling step ground motions which have low PGV/PGA, enforce larger deformation and internal forces over the structure than the forward directivity motions (fig. 5) (Li et al, 2017;Hajali et al, 2018).…”
Section: Effect Of Near-fault Earthquake On Bridge Structuresmentioning
confidence: 99%
“…The seismic response of a near-fault ground motion differs significantly from far-fault earthquakes (Akkar et al, 2005;Adanur et al, 2012). NFGM exposes structures to a large amount of energy at the start of the earthquake due to a large velocity pulse, resulting in an increase in structural responsiveness with considerable structural damage (Liao et al, 2004;Davoodi et al, 2013;Hajali et al, 2018). It has been observed that in comparison to half-wave signals, a pulse including a full-wave signal causes severe structural damage (Reddy et al, 2011).If the pulse velocity's Time Period (T p ) is longer than the structure's fundamental Time period (T 1 ), the structure's seismic demand in the elastic range increases.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity pulse effect and the high-frequency vibration are the main characteristics of near-fault earthquakes. Several scholars have studied the influence of the velocity pulse on the structural response, finding that the velocity pulse effect usually causes a larger response than the non-pulse far-field earthquake (Hajali et al, 2018; Jalali et al, 2012; Süleyman et al, 2012; Wu et al, 2014; Xin et al, 2019; Yan and Chen, 2015; Zhang et al, 2018), but most scholars pay attention to long-period structures such as high-rise buildings and large-span structures, it has been found in their researches that the velocity pulse plays a controlling role on the seismic response of these long-period structures, while the high-frequency vibration has little effect. Furthermore, it shows that the seismic response of structure under the near-fault earthquake is associated with the structural period.…”
Section: Introductionmentioning
confidence: 99%